2015
DOI: 10.1021/acs.joc.5b02203
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Stereodirecting Participation by 2-O-Alkoxycarbonylmethyl Ethers in 4,6-O-Benzylidene-Directed Mannosylation

Abstract: The preparation of a series of mannopyranosyl donors carrying 2-O-(2-oxoalkyl) ethers and their use in glycosylation reactions is described. The formation of cyclic products with the simple 2-O-phenacyl ether and with the 2-O-(t-butoxycarbonylmethyl) ether establishes the stereoelectronic feasibility of the participation in such systems. The high β-selectivities observed with the bis-trifluoromethyl phenacyl ether indicate that participation can be suppressed through the introduction of electron-withdrawing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…With the corresponding donors protected with an allyl ether at the 3-position, the same overall trends were observed but selectivities did not exceed 5:1 for either the R-or S-configured system, and in the case of a less reactive intercept the activated glycosyl donor without need for extensive conformational distortion of the pyranoside ring. 165 In these experiments stereodirecting participation was envisioned to afford the axial glycosides, while its absence was expected to afford the equatorial glycosides by the well-established glycosyl triflate mechanism. In the event, activation of the 2-O-phenacyl-mannosyl thioglycoside with triflic anhydride and diphenyl sulfoxide at -78 °C in dichloromethane followed by the addition of 1adamantanol resulted in the isolation of a cyclic product in 33% yield, thereby establishing that the stereoelectronic requirements for participation were met by this class of probe (Scheme 14).…”
Section: Participation By 2-o-alkoxyacetyl Ethers and Phenacyl Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…With the corresponding donors protected with an allyl ether at the 3-position, the same overall trends were observed but selectivities did not exceed 5:1 for either the R-or S-configured system, and in the case of a less reactive intercept the activated glycosyl donor without need for extensive conformational distortion of the pyranoside ring. 165 In these experiments stereodirecting participation was envisioned to afford the axial glycosides, while its absence was expected to afford the equatorial glycosides by the well-established glycosyl triflate mechanism. In the event, activation of the 2-O-phenacyl-mannosyl thioglycoside with triflic anhydride and diphenyl sulfoxide at -78 °C in dichloromethane followed by the addition of 1adamantanol resulted in the isolation of a cyclic product in 33% yield, thereby establishing that the stereoelectronic requirements for participation were met by this class of probe (Scheme 14).…”
Section: Participation By 2-o-alkoxyacetyl Ethers and Phenacyl Ethersmentioning
confidence: 99%
“…These results suggest that while participation by the ester is possible, as revealed by the formation of the lactone from the tert-butyl ester, the incipient bond from the carbonyl group to the anomeric position is weak and the main glycosylation pathway flows through the typical glycosyl triflate (Scheme 15). 165 This conclusion cannot be extrapolated directly to the analogous Boons system (Scheme 13) 89 because of the presence of the additional phenyl substituent in the latter, which potentially accelerates cyclization through a Thorpe Ingold-gem-dimethyl type conformational effect. deuteriochloroform.…”
Section: Scheme 14 Stereodirecting Participation By 2-o-phenacyl Groups Is Dependent On the Electron Density Of The Aryl Groupmentioning
confidence: 99%
“…The Crich group furthermore released -selective mannopyranosylation of thioglycoside derivatives to generate mannopyranosides. 96 Scheme 55. Sialylation of various sugar acceptors with sialyl sulfoxide.…”
Section: Thionium Reagentsmentioning
confidence: 99%
“…Stereoselective glycosylation has been extensively studied due to the biological significance of glycosylated products; however, it remains a challenging synthetic transformation in the field of carbohydrate chemistry. [94][95][96] Recently, -selective sialylation of sialic acids has attracted significant attention from many researchers. Employing the Tf 2 O/(Tol) 2 SO activation strategy, Xing and co-workers demonstrated that N-acetyl-5-N,4-O-oxazolidinone-protected sialyl sulfoxide 55a activated by Tf 2 O could be converted into natural (2,6)-, (2,3)-, and (2,4)-sialosides 55b with high -selectivity (Scheme 55).…”
Section: Thionium Reagentsmentioning
confidence: 99%
“…[10] Related probes subsequently revealed that participation through fused six-membered dioxacarbenium ions appended to the 2-position is also unlikely. [11] Numerous studies have resulted in the isolation of bridged bicyclics pecies from DGP by remote trichloroacetimidates,b ut such groups are more nucleophilic than carboxylate esters,a nd the conditions employed typically more forcing than standard glycosylation reactions. [3] The recent characterization of am acrocyclic acetal stemming from DGP by the ketone moiety in aremote levulinate ester, in the presence of multiple esters capable of NGP and DGP,is also noteworthy.…”
Section: Introductionmentioning
confidence: 99%